The use of poetry to enhance motivation in tenth graders - Paz González, Julio César (Universidad de Ciencias Pedagógicas "Félix Varela Morales", 2011)
The National System of Education is involved in a process of transformations. The changes taking place in the pre university level are aimed at preparing the students for their insertion in society. In order to attain these goals, the Cuban pre university has turned into a more flexible, wide-ranging and open institution. The subject of English has been included within the syllabus of this level. But, teachers frequently discover that pre university students complain about the English lessons. In this paper, the author searched for ways to address the problem of how to motivate the students to get more involved within the English lessons at this level. This paper offers a system of learning tasks on poetry as a tool to motivate 10th grade students within the teaching learning process of English
Keywords: Pre Universitario; Inglés; Idiomas; Enseñanza